Association Between Phosphorylated Histone H3 and Oncotype DX Recurrence Scores in Breast Cancer. Issue 1 (January 2017) - Lee, Lik Hang; Swanson, Paul E.; Tang, Patricia A.; Bigras, Gilbert; Yang, Hua
Abstract : We investigate the association between phosphorylated histone H3 (PhH3) and Oncotype DX recurrence score (RS). All invasive breast carcinoma with RS results from our city between 2007 and 2010 (n=47) were reviewed. Whole-tumor sections were stained for PhH3. Mitotic and PhH3 counts were performed and clinical charts reviewed. PhH3 correlated well with RS ( r =0.69, P <0.001). Other correlations were: PhH3 versus mitotic count ( r =0.87, P <0.001), PhH3 versus mitotic score ( r =0.71, P <0.001), PhH3 versus modified Bloom-Richardson-Elston (MBR) grade ( r =0.65, P <0.001), RS versus mitotic count ( r =0.62, P <0.001), RS versus mitotic score ( r =0.44, P =0.002), and RS versus MBR grade ( r =0.49, P =0.001). Significant correlation between PhH3 and RS remained after controlling for mitotic count ( r =0.39, P =0.007), mitotic score ( r =0.60, P <0.001), MBR grade ( r =0.56, P <0.001), and all 3 (r=0.37, P =0.014) by partial correlation. Two patients died of metastasis at 12 and 38 months after diagnosis. One had intermediate RS, and 1 high RS; both were in the top-third of PhH3 count. All other patients are alive and recurrence free. Correlation between PhH3 and RS was statistically significant in our cohort, and remained significant after controlling for traditional measures of proliferation. Given that RS has an established strong relationship with prognosis and therapy responsiveness, PhH3 may thus also be an important prognostic/predictive marker in breast cancer.